Disiplin Karyawan Mempengaruhi Kualitas Produksi Blimbing Petani Ratu Buah di Blitar (Studi pada Bisnis Keluarga di Kec Sukorejo Desa Karangsari Blitar) - Sumarsasi, Sumarsasi (Akutansi Bisnis & Manajemen ( ABM ), 2017)
In managing Human Resource management both done in companies and organizations require discipline in achieving production quality targets that can make a flourish, although companies or organizations have clear goals and programs. If not supported by employee discipline which is one key to success then the company or organization will not work optimally. The higher the employee discipline the more optimal the production quality targets produced. But it is difficult to apply to organizations or companies, let alone those that are managed in a kinship